Pengaruh Rasio Likuiditas, Profitabilitas Dan Pertumbuhan Penjualan Terhadap Harga Saham PT Sido Muncul, Tbk - Nurhidayanti (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this study was to find the effect of Current Ratio, Return On Asset (ROA) and Sales Growth on PT Sido Muncul Tbk's Stock Price from 2012-2021. The research method used is the associative method which measures the effect of the ratio on stock prices using secondary data derived from The company's financial statements. The data analysis techniques used are Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test and Hypothesis Testing with t test and F test. The results show that Current Ratio and Sales Growth have no effect on stock prices while Return on Assets ( ROA) has an effect on stock prices.